Clinical and economic analysis of outcomes of dose tapering or withdrawal of tumor necrosis factor-α inhibitors upon achieving stable disease activity in rheumatoid arthritis patients - Aletaha D; Snedecor SJ; Ektare V; Xue M; Bao Y; Garg V (Dove Medical Press, 2017)
Daniel Aletaha,1 Sonya J Snedecor,2 Varun Ektare,2 Mei Xue,2 Yanjun Bao,3 Vishvas Garg3 1Division of Rheumatology, Department of Internal Medicine, Medical University of Vienna, Vienna, Austria; 2Pharmerit International, Bethesda, MD, 3AbbVie Inc., North Chicago, IL, USA Objective: To compare the real-world, 5-year clinical and cost impact of maintaining treatment with the tumor necrosis factor-α inhibitors (anti-TNFs) adalimumab, etanercept, or infliximab vs dose tapering or withdrawal in rheumatoid arthritis (RA) patients who have achieved remission (defined as a 28-joint count Disease Activity Score [DAS28] < 2.6) or low disease activity (LDA; DAS28 < 3.2). Methods: Using a 5-year Markov model with 1-month cycle length, we examined the clinical and cost impact of three treatment strategies: withdrawal, tapering, or maintenance of anti-TNFs among RA patients in remission or who have achieved LDA. This model assessed the time to loss of disease control, time to regaining control after treatment reinitiation, and associated medical and anti-TNF costs. To determine the risk of losing disease control, 14 studies (2309 patients) were meta-analyzed, adjusted for treatment strategy, anti-TNF, RA patient type (early or established RA), and model entry criterion (remission or LDA). Results: Anti-TNF withdrawal and tapering incurred comparable 5-year total costs (€37,900–€59,700 vs €47,500–€59,200), which were lower than those incurred by anti-TNF maintenance (€67,100–€72,100). Established RA patients had higher total costs than early RA patients (€45,900–€72,100 vs €37,900–€71,700). Maintenance was associated with the longest time to loss of disease control (range, 27.3–47.1 months), while withdrawal had the shortest (range, 6.9–30.5 months).Conclusion: Dose tapering or withdrawal of anti-TNFs results in similar reduction of health care costs but less time in sustained disease control compared to maintaining therapy. Future research is needed to understand the long-term clinical consequences of these strategies and patient preferences for treatment withdrawal. Keywords: economic analysis, dose reduction, flare, biologics withdrawal